Jesus in the Ṣūfī Interpretations - Selim Çakıroğlu (İslami İlimler Dergisi)
This article aims to examine the Ṣūfī interpretation of the story of the prophet Jesus in the Qurʾān. The fate of Jesus, who came to the world in a miraculous way, resulted in a similar way. The fact that the verses in the Qur’an that mention the Jews wanting to kill him (as well as other verses) do not state what his ultimate fate was has been the focus of much discussion. The interpretations made by the Ṣūfīs, who put forward a different method in the Islamic tafsīr tradition in terms of their interpretation style, contributed to the emergence of original interpretations in Islamic thought. In this article, the approach of the Ṣūfīs in the debates around the issues of “the ascension of Jesus” and “the return of Jesus” in Islamic thought will be outlined, and the interpretations of the Ṣūfīs in terms of their methods in interpreting the stories about Jesus will be examined within the framework of eight leading Ṣūfī tafsīr books.